A selective serotonin reuptake inhibitor ameliorates obsessive–compulsive disorder-like perseverative behavior by attenuating 5-HT2C receptor signaling in the orbitofrontal cortex. (15th March 2022) - Hatakama, Hikari; Asaoka, Nozomi; Nagayasu, Kazuki; Shirakawa, Hisashi; Kaneko, Shuji
Abstract: Perseveration is a characteristic of patients with obsessive–compulsive disorder (OCD). Clinically, neuronal activity in the lateral orbitofrontal cortex (OFC) is increased in OCD patients. Successful treatment with selective serotonin reuptake inhibitors (SSRIs) reduces activity in the lateral OFC of OCD patients, but the precise mechanisms underlying this effect are unclear. Previously, we reported that repeated injection of the dopamine D2 receptor agonist quinpirole (QNP) resulted in OCD-like deficits, including perseveration in a reversal learning task. QNP-treated mice showed hyperactivity in lateral OFC pyramidal neurons. The present study demonstrated that 4-week administration of an SSRI increased the rate of correct choice in a reversal learning task. Using the electrophysiological approach, we revealed that an SSRI decreased the activity of lateral OFC pyramidal neurons in QNP-treated mice by potentiating inhibitory inputs. The 4-week administration of an SSRI inhibited the potentiation of neuronal activity induced by a 5-HT2C receptor agonist. Additionally, both 4-week administration of SSRI and acute application of 5-HT2C receptor antagonist prevented the QNP-induced potentiation of inhibitory inputs to fast-spiking interneurons in the lateral OFC. Administration of a 5-HT2C receptor antagonist to mice for 4 days increased the rate of correct choice in a reversal learning task. Collectively, these results indicate that chronic SSRI ameliorated perseverative behavior in QNP-treated mice by modulating inhibitory inputs in the lateral OFC. Short-term 5-HT2C receptor blockade also ameliorated QNP-induced behavioral and neurological abnormalities by, at least in part, a common mechanism with chronic SSRI. Highlights: Chronic SSRI treatment improved perseverative behavior in a model of obsessive–compulsive disorder (OCD). Chronic SSRI decreased the activity of lateral orbitofrontal cortex (OFC) pyramidal neurons of OCD model mice. Acute 5-HT2C receptor blockade inhibited neuronal hyperactivity in the lateral OFC. Chronic SSRI inhibited activation of lateral OFC pyramidal neurons induced by acute 5-HT2C receptor stimulation. The SSRI blocked inhibitory inputs to fast-spiking interneurons by attenuating 5-HT2C receptor signaling. Acute 5-HT2C receptor antagonist treatment also improved abnormal perseverative behavior.